Assessment of therapeutic strategies for management of impulse control disorder in Parkinson’s disease - Mayela Rodríguez-Violante; Yazmín Ríos-Solís; Oscar Esquivel-Zapata; Fanny Herrera; Susana López-Alamillo; Cynthia Sarabia-Tapia; Amin Cervantes-Arriaga (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Impulse control disorders (ICD) occur frequently in individuals with Parkinson's disease. So far, prevention is the best treatment. Several strategies for its treatment have been suggested, but their frequency of use and benefit have scarcely been explored. Objective: To investigate which strategy is the most commonly used in a real-life setting and its rate of response. Methods: A longitudinal study was conducted. At the baseline evaluation, data on current treatment and ICD status according to QUIP-RS were collected. The treatment strategies were categorized as “no-change”, dopamine agonist (DA) dose lowering, DA removal, DA switch or add-on therapy. At the six-month follow-up visit, the same tools were applied. Results: A total of 132 individuals (58.3% men) were included; 18.2% had at least one ICD at baseline. The therapeutic strategy most used in the ICD group was no-change (37.5%), followed by DA removal (16.7%), DA switch (12.5%) and DA lowering (8.3%). Unexpectedly, in 20.8% of the ICD subjects the DA dose was increased. Overall, nearly 80% of the subjects showed remission of their ICD at follow-up. Conclusions: Regardless of the therapy used, most of the subjects presented remission of their ICD at follow-up Further research with a longer follow-up in a larger sample, with assessment of decision-making processes, is required in order to better understand the efficacy of strategies for ICD treatment.